The Effect of Competence and Work Environment on Performance Through Self Efficacy (Case Study of Frontliner Employees PT. Bank Rakyat Indonesia Tbk, Masohi Branch, Central Maluku) - Thalia M. Manusiwa; Conchita V. Latupapua; Gerrit M. Pentury (Sean Institute, 2025)
This study aims to test and analyze the influence of competence, work environment, and self-efficacy on performance, test and analyze the influence of competence and work environment on self-efficacy, test and analyze the influence of competence and work environment on performance through self-efficacy. This study was conducted on employees of PT Bank Rakyat Indonesia Tbk, Masohi Branch, Central Maluku. The population was 48 employees. The sampling technique used was a census. The research method used was a quantitative research method. The distribution of questionnaires was measured using a Likert scale. The data analysis method used toolsPartial Least Square analysis which is processed using Smart PLS software version 3.The results of the study show that competence, work environment, and self-efficacy have an effect on performance, the results of the study show that competence does not have an effect on self-efficacy, the results of the study show that the work environment has an effect on self-efficacy, the results of the study show that competence does not have an effect on performance through self-efficacy, the results of the study show that the work environment has an effect on performance through self-efficacy.